Taxonomic review of the terrestrial planarian genus Issoca Froehlich, 1955 (Platyhelminthes, Tricladida, Geoplaninae) and related species - Araujo, Ana Paula Goulart (2021)
The systematics of the Neotropical land planarian genera Luteostriata, Winsoria, Issoca and Supramontana (Platyhelminthes, Tricladida, Geoplaninae) -abbreviated LWIS- is weak since the genera are diagnosed by rather similar features, only varying in the details. The systematics of LWIS is revised through a morphological and molecular approach. Four species of Issoca are redescribed by studying the type specimens and/or additional material prepared on histological slides or through micro-computed tomography. The molecular phylogenetics retrieved (a) LWIS and all 13 species studied as monophyletic, (b) Issoca rezendei as sister to the remaining LWIS, (c) Issoca and Luteostriata polyphyletic and (d) Winsoria and Supramontana nested each within the respective heterogenous clade with respect to the species composition. Despite the low statistical support for some clades, the phylogeny is congruent with the morphology of the species. Morphologically, Issoca rezendei stands apart from the other species of LWIS and a rediagnosis of the genus is proposed. The remaining LWIS members are placed into Supramontana, which is also rediagnosed, and Luteostriata and Winsoria are considered junior synomyms. Finally, four new species of Supramontana are described.